Entrepreneurial opportunity decisions under uncertainty: Recognizing the complementing role of personality traits and cognitive skills - Emmanuel Kwasi Mensah; Lawrence Adu Asamoah; Vahid Jafari-Sadeghi (Journal of Entrepreneurship, Management and Innovation)
Purpose: The aim of this paper focuses on advancing the entrepreneurial literature by enhancing the understanding of the connections between personal behavior and cognitive skills in decision making under uncertainty. Methodology: The method of this research has been adapted the framework used by Garrett and Holland (2015), who developed propositions from the conceptual narratives of how environmental uncertainty and complexity differentially affect the motivations and cognition of independent entrepreneurs and corporate entrepreneurs to engage in entrepreneurial action. Findings: The findings of this research provide a conceptual basis for a broader perspective on behaviors and cognitions that motivate or hinder entrepreneurial actions while at the same time, positioning the entrepreneur’s decision at the core of decision theory. Implications for theory and practice: Theoretically, this research contributes to a holistic view of opportunity decisions. It redirects the traditional analyses path of entrepreneurial decisions discussed distinctively from the personal behavior or cognition paradigm, which does not provide a complete view into the larger entrepreneurial decisions under uncertainty. Practically, our argument provides further insight into the black box of entrepreneurial opportunity decisions under uncertainty and thus highlights the need for a broader perspective for the entrepreneur, especially in the early stage of venture formation, where some cognitions and required personal attributes are needed in consonance for entrepreneurial action. Originality and value: Entrepreneurship research on decision making under uncertainty has mainly focused on the effect of uncertainty on entrepreneurial actions, while an attempt at the individual level, particularly, from the cognitive framework seeks to explain why actions differ. Scholarly efforts have also been made on what informs entrepreneurial actions from the perspective of the entrepreneur’s personal attributes. However, no integrated approach is offered in the literature to study how cognitive skills and personality traits complement each other.